Effect of Dissolved Oxygen and Temperature on Macromolecular Composition and Phb Storage of Activated Sludge - Montalvo-Martinez, S (Taylor and Francis Inc., 2014)
The macromolecular composition of activated sludge (lipids, intracellular proteins and intracellular polysaccharides) was studied together with its capacity to store macromolecules such as polyhydroxybutyrate (PHB) in a conventional activated sludge system fed with synthetic sewage water at an organic load rate of 1.0 kg COD/(m3·d), varying the dissolved oxygen (DO) and temperature. Six DO concentrations (0.8, 1.0, 1.5, 2.0, 2.5 and 8 mg/L) were studied at 20°C with a sludge retention time (SRT) of 6 days. In addition, four temperatures (10C, 15C, 20C and 30C) were assessed at constant DO (2 mg/L) with 2 days SRT in a second experimental run. The highest lipid content in the activated sludge was 95.6 mg/g VSS, obtained at 30°C, 2 mg/L of DO and a SRT of 2 days. The highest content of intracellular proteins in the activated sludge was 87.8 mg/g VSS, obtained at 20°C, 8 mg/L of DO and a SRT of 6 days. The highest content of intracellular polysaccharides in the activated sludge was 76.6 mg/g VSS, which was achieved at 20°C, a SRT of 6 days and a wide range of DO. The activated sludge PHB storage was very low for all the conditions studied. © 2014 Copyright Taylor & Francis Group, LLC.
Keywords: macromolecular composition; temperature; dissolved oxygen; PHB; Activated sludge